The current landscape of CRISPR-Cas9-based technologies for imaging of genomic loci in fixed and live cells - Yu, Choo Yee; Yean, Chan Yean; Chan, Kok Gan; Ang, Geik Yong (Xia and He Publishing Inc., 2024)
Visualization of the spatiotemporal organization and dynamics of the genome in the nucleus is essential to elucidate how chromatin structure and nuclear function are intertwined. In the past, such studies were limited by the lack of appropriate tools. However, various imaging techniques now allow direct visualization of genomic loci in living cells. One of the main drivers behind this progress is the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated proteins (Cas) technology. Initially used as an efficient and specific genome editing tool, the versatility of the CRISPR/Cas system has rapidly expanded its application range to include diagnostics, therapeutics, and, more recently, live cell imaging. In contrast to traditional fluorescent in situ hybridization, CRISPR/Cas-based imaging systems enable real-time dynamic tracking of genomic sequences down to the level of single cells and even a single locus. Recognizing the vital role played by CRISPR/ Cas-based imaging systems in advancing our understanding of genome function in relation to its spatiotemporal organization, this review aimed to depict the current landscape of CRISPR/Cas-based technologies in genomic imaging. It discusses the principles, notable features, advantages, and limitations of these CRISPR/Cas-based imaging systems and concludes with a brief outlook into the future.